Cytomegalovirus infection and immune-mediated inflammatory rheumatic diseases: what is known today - B. S. Belov; N. V. Muravyova (Современная ревматология, 2024)
Cytomegalovirus (CMV) infection is a common viral anthroponotic infection characterized by a variety of clinical and laboratory symptoms. There is a growing body of data on the association between CMV and the development of immune-mediated inflammatory rheumatic diseases (IIRD). The presence of immunopathological disorders caused both by the disease itself and using drugs with immunosuppressive effect determines the relatively high prevalence of comorbid active CMV in patients with IIRD. The commonality of the clinical picture of CMV infection and individual IIRDs often leads to problems in the diagnosis and differentiation between these diseases. The lack of recommendations for the rational use of antiviral drugs for therapeutic and prophylactic purposes in IIRD calls for further research.